2017
DOI: 10.1177/1479972317736293
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory biomarkers and radiologic measurements in never-smokers with COPD: A cross-sectional study from the CODA cohort

Abstract: Various biomarkers have emerged as potential surrogates to represent various subgroups of chronic obstructive pulmonary disease (COPD), which manifest with different phenotypes. However, the biomarkers representing never-smokers with COPD have not yet been well elucidated. The aim of this study was to evaluate the associations of certain serum and radiological biomarkers with the presence of COPD in never-smokers. To explore the associations of serum and radiological biomarkers with the presence of COPD in nev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…A total of 20 articles were retrieved for full-length article review and 12 articles were excluded at this stage as they did not report the level of serum uric acid among participants with and without COPD. Finally, eight studies [12][13][14][15][16][17][18][19] with 1,612 participants were eligible for the meta-analysis. The literature retrieval, review and selection process are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 20 articles were retrieved for full-length article review and 12 articles were excluded at this stage as they did not report the level of serum uric acid among participants with and without COPD. Finally, eight studies [12][13][14][15][16][17][18][19] with 1,612 participants were eligible for the meta-analysis. The literature retrieval, review and selection process are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…A sensitivity analysis was conducted to exclude two studies [17][18] that reported median and interquartile range and, thus, mean and SD had to be approximated using the technique described under Methods. Exclusion of these two studies from the pooled analysis only slightly increased pooled MD to 1.16 and remained statistically significant (95% CI: 0.57-1.75; I 2 88%), suggesting that the approximation did not have a substantial impact on the pooled result (supplementary data 3).…”
Section: Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The cohort was created to observe the clinical outcomes of patients with COPD living near cement plants in Korea, as previously described. 11 The CODA cohort recruited COPD patients in Kangwon University Hospital from 2012 until the end of 2015. The patients were recruited from six administrative districts of Korea where cement plants were located.…”
Section: Methodsmentioning
confidence: 99%
“…High uric acid was signifi cantly associated with the presence of COPD in never-smokers after multivariate analysis ( Table 1). 52 MARKERS OF COPD EMPHYSEMA PHENOTYPE Papaioannou et al evaluated the associations of eosinophils with the presence of emphysema in COPD patients. 53 Sputum and blood eosinophil counts, lung function testing and high resolution computed tomography (HRCT) of the chest were performed.…”
Section: Clinical and Immunological Markers Of Copd Never-smoker Phenmentioning
confidence: 99%